The Concept of Reconciliation in Islamic Criminal Law and the Implementation of Restorative Justice as a Contribution to Criminal Law Reform in Indonesia - Hendra Prayoga; Wasman; Edy Setyawan (MIZAN: JOURNAL OF ISLAMIC LAW, 2025)
The criminal law system in Indonesia tends to be retributive, with the main focus on sanctioning the perpetrators of criminal acts. This approach is often unable to provide a comprehensive solution to the losses suffered by victims and the restoration of disrupted social relations. In this context, the restorative justice approach comes as a more humanist alternative, with an emphasis on victim recovery, offender accountability, and social reconciliation. Interestingly, the principles of restorative justice are in line with the values in Islamic criminal law, particularly in the concept of ishlah (peace), which provides ample room for the settlement of criminal cases through peace between perpetrators and victims. This concept is in line with the main principles of restorative justice, namely the restoration of social relations, active participation of the parties, and recovery of victims. In Indonesia, the application of restorative justice has begun to be accommodated in various regulations, such as the National Police Chief Regulation Number 8 of 2021 and the new Criminal Code, but its implementation still faces normative and cultural challenges. Keywords: Peace; Islamic Criminal Law; Restorative Justice; and Legal Reform.